Engineering mechanics : statics & dynamics - Costanzo, Francesco, 1964-; Plesha, Michael E.; Gray, Gary L. (New York : McGraw-Hill Higher Education, 2010)
This is a full version; do not confuse with 2 vol. set version (Statistics 9780072828658 and Dynamics 9780072828719) which LC will not retain.
Includes index
Keywords: Mechanics, Applied -- Textbooks